Preparation of a working seed lot of BCG and quality control by PCR genotyping - Trovero, A. (2010)
The bacillus Calmette-Guérin (BCG) was obtained in 1920 after successive passages leading to the attenuation of a Mycobacterium bovis strain. For the following 40 years, BCG had been replicated, resulting in substrains with genotypic and phenotypic differences. Several genomic studies have compared two BCG strains, M. bovis and Mycobacterium tuberculosis, and observed that deleted regions in the different strains could be related to differences in antigenic properties. In this work, a working seed lot was obtained from a lyophilized secondary seed lot from the BCG Pasteur strain 1173 P2 and genetically characterized. The genome was analyzed by PCR directed to five regions (RD1, RD2, RD14, RD15, DU2), using the seed lot and different available strains as templates. No genetic differences were found in the fragments studied as compared to the Pasteur strain. A total of 20 passages were carried out and no differences were found in the size of the fragments amplified by PCR. In conclusion, this method allows to control a working seed lot genotypically and to assess the stability of the BCG genome.